2016
DOI: 10.5946/ce.2015.049
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Submucosal Dissection for Early Gastric Neoplasia Occurring in the Remnant Stomach after Distal Gastrectomy

Abstract: Background/Aims:Endoscopic submucosal dissection (ESD) for tumors occurring in the remnant stomach is technically difficult to perform because of limited working space and severe fibrosis and staples present around the suture line. We aimed to elucidate the feasibility and clinical outcomes of performing ESD for tumors in the remnant stomach.Methods:Between December 2007 and January 2013, 18 patients underwent ESD for tumors (six adenomas and 12 differentiated-type early gastric cancers [EGCs]) occurring in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…This is consistent with previous results indicating the absence of recurrence during a median follow-up of 47.5 months [11] and a 3-year overall survival rate of 85%, with 8 deaths due to other causes and none due to gastric cancer [13]. Considering the high postoperative mortality (19%–41%) after radical total gastrectomy for cancer in the remnant stomach [24, 25] and the favorable long-term outcomes in our study, ESD appears to be an attractive alternative to completion total gastrectomy, irrespective of the type of previous gastrectomy.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is consistent with previous results indicating the absence of recurrence during a median follow-up of 47.5 months [11] and a 3-year overall survival rate of 85%, with 8 deaths due to other causes and none due to gastric cancer [13]. Considering the high postoperative mortality (19%–41%) after radical total gastrectomy for cancer in the remnant stomach [24, 25] and the favorable long-term outcomes in our study, ESD appears to be an attractive alternative to completion total gastrectomy, irrespective of the type of previous gastrectomy.…”
Section: Discussionsupporting
confidence: 94%
“…Similarly, in the present study, perforation occurred in 1 patient whose lesion involved the suture lines. Overall, the perforation rate was only 3%, which is similar to rates reported previously (1.4%–5.6%) [10, 11]. This can be explained by the low number of lesions involving the suture lines, in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Referring to other studies reported in Korea, the number of metachronous adenomas and cancers after DG was 18 and 12 (however, in this study, the incidence of metachronous neoplasms could not be identified since only cases treated with endoscopic submucosal dissection were collected). 45 And Kim et al 37 reported that the incidence of metachronous neoplasms after endoscopic treatment for gastric dysplasia was 11.0%, and the number of metachronous adenomas and cancers was 24 (18 low-grade adenomas and six high-grade adenomas) and three, respectively. Although the number of MGNs in patients received surgery might be smaller due to the decreased area of the remnant stomach after surgery, the ratio of adenoma and cancer could be similar.…”
Section: Discussionmentioning
confidence: 99%
“…The most important step of these operations is to pull out the ANs. Unlike forcibly extracting the ANs using alligators or forceps in ESD for early gastric remnant cancer or colorectal MECPL emerging at the AS reported in the previous studies (8,9,18,25,26), the key and innovative point of our method is to integrate the nail and electrical knife by means of the electrical conduction effect (see in Figure 1B). Then, the submucosal tissue can be stripped around the ANs step by step, and finally, the ANs can be gently and successfully pulled out (see in Figure 1C).…”
Section: Discussionmentioning
confidence: 99%